KONSEP ILMU (KEISLAMAN) AL-GHAZALI DALAM PERKEMBANGAN PENDIDIKAN ISLAM MASA KINI - Rusli Rusli; Lahmuddin Lahmuddin; Rubino Rubino (Sekolah Tinggi Agama Islam Al Hidayah, 2014)
Al-Ghazali view for Islamic Education Development is very important at present day. Imam Al-Ghazali is intellect people and his name is familiar at Moslems. He is expert in philosophy and tasawuf. Imam Al-Ghazali to look at education as media to approach to Allah Subhanahu wa Ta’ala and to get happiness in the world and in the future. As we know from his goal educations that Insan Purna where the goal to approach Allah Subhanahu wa Ta’ala and to get happiness in the world and in the future.As Al-Ghazali ideas for example, there are no separation between religion knowledge and general knowledge. There are three points of Al-Ghazali ideas about education at Ihya book: explanation about knowledge is better than dumbness, codification in knowledge and ethic for teacher and student. As Al-Ghazali idea, if people just study about general knowledge without religion knowledge is no benefit anything in the future.Al-Ghazali use Mujahadah method and Riyadhah method, discipline method, naqli and aqli method, guidance and advice method in teaching method. In teaching media, he agrees with reward and punishment, and must be good personality. Success and failure at education process generally depend on output. Success education if output from education is responsible people to people and to God, and give benefit to himself.